Androgen-deprivation therapy boosts MX1 expression, a silent effector against COVID-19 - Sanchis, Pablo Antonio (2020)
Cancer is a risk factor for SARS-CoV-2 infection. Recent reports have shown that prostate cancer (PCa) patients undergoing androgen-deprivation therapies (ADT) were partially protected from COVID-19. The human myxovirus resistance gene 1 (MX1) is expressed in many tissues, including prostate, and we have previously demonstrated its antitumoral activity in PCa, tilting the balance of endoplasmic reticulum stress towards pro-death events. Another key aspect of this protein is its participation in the antiviral response. It is recognized as an IFN-stimulated gene (ISGs), especially during influenza virus infection. Currently, there are several ongoing clinical trials for COVID-19 prevention and/or treatment using type I or III interferons. However, IFN administration could enhance a "cytokine-storm" causing a hyper-inflammatory response and contributing to multiple organ failure. In this work, we performed bioinformatics analyses in a case-control study from SARS-CoV-2 positive (n=403) and negative (n=50) patients. We analyzed the response to infection assessing gene expression profiles in nasopharyngeal swabs of key host cell receptors (ACE2, TMPRSS2, BSG/CD147, CTSB, CTSL, ADAM17) and antiviral proteins (MX1, MX2, NRF2, IRF3, HIF1A, HMOX1). The expression analysis associated with reported risk factors for COVID-19 was also assessed.SARS-CoV-2 positive cases had higher ACE2, but lower TMPRSS2, BSG/CD147 and CTSB expression compared with negative cases. Patient age negatively affected ACE2 expression. MX1 and MX2 were higher in SARS-CoV-2 positive individuals, and negative trends were observed as patients? age increased. Principal Component Analysis determined that ACE2, MX1, MX2 and BSG/CD147 expressions were able to cluster non-COVID-19 and COVID-19 individuals. Multivariable regression showed that MX1 expression significantly increased for each unit of viral load increment. Given that MX1 was differentially expressed between COVID-19 and non-COVID-19 patients, we evaluated MX1 expression in A549 and Calu3 lung cell lines. MX1 was significantly up-regulated upon infection with SARS-CoV-2.Because ADT reduces SARS-CoV-2 infection incidence, we aim to study MX1 regulation by dihydrotestosterone (DHT). We browsed publicly available ChIP-seq experiments evaluating androgen receptor (AR) binding sites in different PCa cell lines under DHT stimulation. Results indicated enriched AR binding sites on the MX1 sequence. Therefore, we treated LNCaP cells with DHT, observing a significant decrease in MX1 mRNA levels. Accordingly, we observed a significant increase of MX1 gene expression in PCa patients after ADT treatment.In summary, our study findings support differences in ACE2, MX1, MX2 and BSG/CD147 expression between COVID-19 and non-COVID-19 patients; and point out to MX1 as a critical responder in SARS-CoV-2 infection. Furthermore, we demonstrated MX1 modulation by ADT. Taking into consideration the fact that PCa patients that underwent ADT were less prone to present the infection, we propose this gene as an alternative druggable target for COVID-19 patients, especially those with PCa as a previous condition.